2015
DOI: 10.1128/jvi.02977-14
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoprotein M Facilitates Enterovirus Infection

Abstract: Picornavirus infection involves a dynamic interplay of host and viral protein interactions that modulates cellular processes to facilitate virus infection and evade host antiviral defenses. Here, using a proteomics-based approach known as TAILS to identify protease-generated neo-N-terminal peptides, we identify a novel target of the poliovirus 3C proteinase, the heterogeneous nuclear ribonucleoprotein M (hnRNP M), a nucleocytoplasmic shuttling RNA-binding protein that is primarily known for its role in pre-mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 74 publications
0
80
0
Order By: Relevance
“…We also showed that CVB3-encoded proteinases cleave RIP1 and RIP3, 2 upstream protein kinases known to regulate NLRP3 inflammasome activity on RNA virus challenge (39), and knockdown of RIP1/RIP3 results in decreased IL-1b production. We recently reported that poliovirus proteinases also directly cleave RIP1 and RIP3 (45). Moreover, it was demonstrated that MAVS interacts with and activates the NLRP3 inflammasome (46,47), and mitofusin 2 is required for MAVS-mediated activation of the NLRP3 pathway after RNA virus infection (48).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that CVB3-encoded proteinases cleave RIP1 and RIP3, 2 upstream protein kinases known to regulate NLRP3 inflammasome activity on RNA virus challenge (39), and knockdown of RIP1/RIP3 results in decreased IL-1b production. We recently reported that poliovirus proteinases also directly cleave RIP1 and RIP3 (45). Moreover, it was demonstrated that MAVS interacts with and activates the NLRP3 inflammasome (46,47), and mitofusin 2 is required for MAVS-mediated activation of the NLRP3 pathway after RNA virus infection (48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to RNA splicing and localization to the nucleus, Jan et al . reported that hnRNP M is a target of poliovirus 3C proteinase and this activity then facilitates enterovirus infection24. Furthermore, utilizing pull-down and mass-spectrometry approaches, Luo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Virus infection was performed as described in reference 60. HeLa cells (already existing collection in the Jan laboratory) were maintained as described previously (90).…”
Section: Methodsmentioning
confidence: 99%